The Role of Literacy and Government Support in Improving MSME Performance Through Digital Financial Services Adoption and Financial Inclusion - Sholihah, Erlinda; Nurhapsari, Risma; Rohmania, Aftuqa Sholikatur (University of Merdeka Malang, 2023)
This study aims to identify the role of financial literacy, digital literacy, and government support mediated by digital financial services adoption and financial inclusion in influencing the financial performance of MSMEs in Central Java. The model in this study was developed from the RBV (Resource Based View) theoretical framework. This study is a type of quantitative study with an explanatory design. The population determined is MSMEs in the food and beverage sector of Central Java Province. The sample was selected using a simple random sampling of 238 respondents using Google Forms. Next, the data analysis technique used SEM-PLS with SmartPLS 3. This study found that financial literacy, government support, digital financial services adoption, and financial inclusion determine the financial performance of MSMEs. These four factors show a significant influence. On the contrary, digital literacy did not significantly affect MSMEs’ financial performance. This research contribution is theoretically expected to be useful in developing RBV (Resource Based View) theory. In addition, it is a direction for three parties (government, entrepreneurs, and financiers) in formulating policies related to strategies to optimize MSMEs’ financial performance based on digital technology. DOI: 10.26905/jkdp.v27i3.11147